Penyisihan Polutan pada Palm Oil Mill Effluent (POME) Menggunakan Konsorsium Mikroalga-Bakteri dengan Sistem High Rate Algae Reactor (HRAR) - Shinta Elystia; Vonny Meidina Rizani; Sri Rezeki Muria (LPPM Universitas Mataram, 2021)
Palm oil mills in addition to producing crude palm oil also produce by-products in the form of Palm Oil Mill Effluent (POME). POME contains high amounts of organic ingredients and pollutants. One method that can be applied to treat POME is the High Rate Algae Reactor (HRAR) System. The HRAR system uses microalgae-bacterial consortium that has better performance in removing pollutants in POME and increasing the growth of microorganisms. This research aim by determining the effect of microalgae suspension concentration in the HRAR system towards the removal efficiency of Chemical Oxygen Demand (COD) and total nitrogen. The research was conducted in batch in the HRAR system that equipped with a paddle wheel, by variations of microalgae suspension concentration as 0; 10; 15; 20; and 25 (% v/v). The research was carried out for 7 days and used the sun as a source of light. Based on the research results, 25% of microalgae suspension concentration has the highest microalgae cell density, was 6,34 x 106 cells/mL and showed the best removal efficiency of COD and total nitrogen, were 78.79% and 80.37%.